Hereditary ovarian carcinoma: Heterogeneity, molecular genetics, pathology, and management - Lynch, Henry T.; Casey, Murray Joseph; Snyder, Carrie L.; Bewtra, Chhanda; Lynch, Jane F.; Butts, Matthew; Godwin, Andrew K. (Molecular oncology, 2009)
Hereditary ovarian cancer accounts for at least 5% of the estimated 22,000 new cases of this disease during 2009. During this same time, over 15,000 will die from malignancy ascribed to ovarian origin. The bulk of these hereditary cases fits the hereditary breast–ovarian cancer syndrome, while virtually all of the remainder will be consonant with the Lynch syndrome, disorders which are autosomal dominantly inherited. Advances in molecular genetics have led to the identification of BRCA1 and BRCA2 gene mutations which predispose to the hereditary breast–ovarian cancer syndrome, and mutations in mismatch repair genes, the most common of which are MSH2 and MLH1, which predispose to Lynch syndrome. These discoveries enable relatively certain diagnosis, limited only by their variable penetrance, so that identification of mutation carriers through a comprehensive cancer family history might be possible. This paper reviews the subject of hereditary ovarian cancer, with particular attention to its molecular genetic basis, its pathology, and its phenotypic/genotypic heterogeneity.